2006
DOI: 10.1249/01.mss.0000229567.09661.20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fatigue on Tibial Impact Accelerations and Knee Kinematics in Drop Jumps

Abstract: Care should be taken when performing drop jumps from a height of 30 cm in a fatigued state because of the reduced capacity to attenuate impact accelerations at the tibia, which may be associated with an increased risk of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
65
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 24 publications
1
65
0
1
Order By: Relevance
“…Moran and Marshall (32) concluded that the increased tibial accelerations after fatiguing exercise indicated a state of increased injury risk when performing SSC activities in a fatigued state. It is important to point out, however, that Moran and Marshall (32) did not obtain measures until at least 2 minutes after the completion of the fatigue protocol; therefore, their findings could equally be explained by a PAP response.…”
Section: Introductionmentioning
confidence: 89%
“…Moran and Marshall (32) concluded that the increased tibial accelerations after fatiguing exercise indicated a state of increased injury risk when performing SSC activities in a fatigued state. It is important to point out, however, that Moran and Marshall (32) did not obtain measures until at least 2 minutes after the completion of the fatigue protocol; therefore, their findings could equally be explained by a PAP response.…”
Section: Introductionmentioning
confidence: 89%
“…impact accelerations) 2 during a series of actions common to their sport and known to be related to injury (e.g. running [3], jumping and landing [6], agility cuts [9]). Generally, the athlete completes 1 − 5 maximum effort trials of each action [6] and their results are compared to normative values, if available [10].…”
mentioning
confidence: 99%
“…running [3], jumping and landing [6], agility cuts [9]). Generally, the athlete completes 1 − 5 maximum effort trials of each action [6] and their results are compared to normative values, if available [10]. These tests are almost exclusively completed in a laboratory since biomechanics based motion analysis systems tend to be camera based (6+ cameras typically) which must remain spatially fixed during the testing session and tend to be negatively affected by changing lighting conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations